Expression of highly compressible materials - Fukuyama, Ryo; Tanaka, Takanori; Yabuta, Nobuyasu; Jami, Mohammed Saedi; Iwata, Masashi (2014)
In the sake brewing, expression is used for the separation of liquid from the fermentation broth. Although the period of expression has to be as short as possible in order to prevent the sake from losing flavour, practically it takes longer time to complete expression because of the highly compressible materials (e.g. proteins and starch) in the broth. For the expression of highly compressible materials, it is known empirically that the applied pressure should be low at the beginning of the expression and raised stepwise as the expression proceeds. In this study, we propose a method for the analysis of the stepwise expression of highly compressible materials.